High catalytic activity of electrochemically reduced graphene composite toward electrochemical sensing of Orange II. (15th February 2015) - Yun, Mira; Choe, Ju Eun; You, Jung-Min; Ahmed, Mohammad Shamsuddin; Lee, Kyungmi; Üstündağ, Zafer; Jeon, Seungwon
Highlights: Covalently bonded ERGO-ATDT-Pt was selectively sensitive to Orange II catalysis. The developed sensor displayed excellent electrocatalytic activity for Orange II. A reversible redox peak current was linearly increased with scan rate. Excellent result was found in real sample analysis. Abstract: Orange II, an azo dye, is sometimes illegally used as a red dye in food products despite its adverse health effects if consumed. Therefore, the determination of low concentrations of Orange II is an important target. An Orange II sensor was prepared using electrochemically reduced graphene oxide grafted with 5-amino-1, 3, 4-thiadiazole-2-thiol-Pt nanoparticles (denoted as ERGO-ATDT-Pt) onto a glassy carbon electrode (GCE) and investigated for Orange II detection in 0.1 M acetate buffer solution (ABS at pH 4.5) with prominent reversible redox peaks. A wide linear range of 1 × 10 − 8 –6 × 10 − 7  M with a low detection limit of 3.4 × 10 − 10  M ( s/n  = 3) was found for Orange II detection. This developed ERGO-ATDT-Pt/GCE sensor showed good selectivity, excellent stability and better response to the real sample analysis with excellent recovery.